Fieldwork in the Sonnet: Milton, Donne, and Critical Orthodoxy - Ullyot, Michael (Renaissance and Reformation / Renaissance et Réforme, 2021)
In this article, Michael Ullyot explores the possible implications for literary reading of a vast textual database of sonnets. Ullyot argues that a growing library of texts and tools will help us to read the sonnet in less linear and more “scalable” ways. Although not fully developed yet, Ullyot’s prototype already has produced useful results by focusing on Milton’s admittedly small corpus of English sonnets. Ullyot suggests that if textual analysis techniques can confirm critical insights about Milton’s sonnets, then more confidence can be placed in these tools and techniques when, later, they are scaled up to larger bodies of texts. While displaying a healthy pragmatic realism about the challenges ahead, Ullyot’s article tantalizingly suggests the scholarly advantages of building the world’s largest sonnet anthology.